2008
DOI: 10.1016/j.bbrc.2007.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Bitter peptides activate hTAS2Rs, the human bitter receptors

Abstract: Fermented food contains numerous peptides derived from material proteins. Bitter peptides formed during the fermentation process are responsible for the bitter taste of fermented food. We investigated whether human bitter receptors (hTAS2Rs) recognize bitterness of peptides with a heterologous expression system. HEK293 cells expressing hTAS2R1, hTAS2R4, hTAS2R14, and hTAS2R16 responded to bitter casein digests. Among those cells, the hTAS2R1-expressing cell was most strongly activated by the synthesized bitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 35 publications
1
64
0
Order By: Relevance
“…Some studies have reported hTAS2R14 to be a broadly tuned receptor. 16,[18][19][20][21] Although the homology between hTAS2R14 and 39 at the amino acid level is only 29%, hTAS2R14 and 39 have such common agonists as quinine, chlorpheniramine, azathioprine, diphenidol, and genistein. 16,20) Furthermore, we revealed in this study that ECg and EGCg were also common agonists to hTAS2R14 and 39.…”
Section: Activation Of the Htas2r14 Human Bitter-taste Receptor By (àmentioning
confidence: 99%
“…Some studies have reported hTAS2R14 to be a broadly tuned receptor. 16,[18][19][20][21] Although the homology between hTAS2R14 and 39 at the amino acid level is only 29%, hTAS2R14 and 39 have such common agonists as quinine, chlorpheniramine, azathioprine, diphenidol, and genistein. 16,20) Furthermore, we revealed in this study that ECg and EGCg were also common agonists to hTAS2R14 and 39.…”
Section: Activation Of the Htas2r14 Human Bitter-taste Receptor By (àmentioning
confidence: 99%
“…29 So the ability to sense bitterness may serve other purposes in addition to poison detection. For instance, when proteins are fermented, some of the protein products are bitter, 30 so the bitter taste system may also detect decayed proteins.…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
“…39 Other bitter molecules stimulate multiple receptors, and the loss of one may decrease but not eliminate the ability to detect that particular bitter molecule. 30,39,47,65-73 The perception of PTC is probably an extreme case of individual variation in bitter perception.…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
“…hT2R46 is a broadly tuned bitter receptor for sesquiterpene lactones, strychnine, and so on [110]. And hT2R1 is tentatively a receptor for bitter peptides [111]. Because of the large family of bitter receptor genes that evolved to recognize bitter sensation from of a wide range of chemicals, identification of ligands for each bitter receptor is necessary to establish the entire bitter tasting profile for humans.…”
Section: Bitter Taste Receptorsmentioning
confidence: 99%
“…These 25 hT2Rs may, in a complementary manner, recognize a specific chemical structure for each receptor to perceive numerous bitter substances. For example, casein hydrolysate, which contains numerous bitter peptides with different structures, can activate several T2Rs [111]. Moreover, two bitter peptides, Gly-Phe and Gly-Leu, also activate all hT2R-expressing cells tested, whereas a nonbitter peptide, Gly-Gly, does not.…”
Section: Perspectivesmentioning
confidence: 99%